Variants that affect function of calcium channel TRPV6 are associated with early-onset chronic pancreatitis - Masamune, Atsushi; Bugert, Peter; Tsvilovskyy, Volodymyr; Freichel, Marc; Kotani, Hiroshi; Sörgel, Franziska Lena; Chen, Jian-Min; Hamada, Shin; Sakaguchi, Reiko; Masson, Emmanuelle; Nakano, Eriko; Kakuta, Yoichi; et al. (Gastroenterology, 2020)
Background & Aims - Changes in pancreatic calcium levels affect secretion and might be involved in development of chronic pancreatitis (CP). We investigated the association of CP with the transient receptor potential cation channel subfamily V member 6 gene (TRPV6), which encodes a Ca2+-selective ion channel, in an international cohort of patients and in mice. - Methods - We performed whole-exome DNA sequencing from a patient with idiopathic CP and from his parents, who did not have CP. We validated our findings by sequencing DNA from 300 patients with CP (not associated with alcohol consumption) and 1070 persons from the general population in Japan (control individuals). In replication studies, we sequenced DNA from patients with early-onset CP (20 years or younger) not associated with alcohol consumption from France (n = 470) and Germany (n = 410). We expressed TRPV6 variants in HEK293 cells and measured their activity using Ca2+ imaging assays. CP was induced by repeated injections of cerulein in TRPV6mut/mut mice. - Results - We identified the variants c.629C>T (p.A210V) and c.970G>A (p.D324N) in TRPV6 in the index patient. Variants that affected function of the TRPV6 product were found in 13 of 300 patients (4.3%) and 1 of 1070 control individuals (0.1%) from Japan (odds ratio [OR], 48.4; 95% confidence interval [CI], 6.3-371.7; P = 2.4 × 10-8). Twelve of 124 patients (9.7%) with early-onset CP had such variants. In the replication set from Europe, 18 patients with CP (2.0%) carried variants that affected the function of the TRPV6 product compared with 0 control individuals (P = 6.2 × 10-8). Variants that did not affect the function of the TRPV6 product (p.I223T and p.D324N) were overrepresented in Japanese patients vs control individuals (OR, 10.9; 95% CI, 4.5-25.9; P = 7.4 × 10-9 for p.I223T and P = .01 for p.D324N), whereas the p.L299Q was overrepresented in European patients vs control individuals (OR, 3.0; 95% CI, 1.9-4.8; P = 1.2 × 10-5). TRPV6mut/mut mice given cerulein developed more severe pancreatitis than control mice, as shown by increased levels of pancreatic enzymes, histologic alterations, and pancreatic fibrosis. - Conclusions - We found that patients with early-onset CP not associated with alcohol consumption carry variants in TRPV6 that affect the function of its product, perhaps by altering Ca2+ balance in pancreatic cells. TRPV6 regulates Ca2+ homeostasis and pancreatic inflammation.
Gesehen am 21.09.2020